High-temperature superconducting screens for magnetic field-error cancellation in accelerator magnets. (24th August 2021) - Bortot, L; Mentink, M; Petrone, C; Van Nugteren, J; Deferne, G; Koettig, T; Kirby, G; Pentella, M; Perez, J C; Pincot, F O; De Rijk, G; Russenschuck, S; et al.
Abstract: Accelerators magnets must have minimal magnetic field imperfections to reduce particle-beam instabilities. In the case of coils made of high-temperature superconducting (HTS) tapes, the magnetization due to persistent currents adds an undesired field contribution, potentially degrading the magnetic field quality. In this paper we study the use of superconducting screens based on HTS tapes for reducing the magnetic field imperfections in accelerator magnets. The screens exploit the magnetization by persistent currents to cancel out the magnetic field error. The screens are aligned with the main field component, such that only the undesired field components are compensated. The screens are self-regulating, and do not require any externally applied source of energy. Measurements in liquid nitrogen at 77 K show for dipole-field configurations a significant reduction of the magnetic field error up to a factor of four. The residual error is explained via numerical simulations accounting for the geometric defects in the HTS screens, achieving satisfactory agreement with experimental results. Simulations show that if screens are increased in width and thickness, and operated at 4.5 K, field errors may be eliminated almost entirely for the typical excitation cycles of accelerator magnets.